Research Gaps In Contaminants Of Emerging Concern (CECs): Routes To The Standardization Of Chemical Test Methods By GC/LC-Mass Spectrometry: A Review - Manickum Thavrin (Journal of New Developments in Chemistry, 2023)
A literature review was undertaken with a focus on 1) identifying the research gaps regarding CECs, 2) identifying the most common ones, and 3) identifying the typical analytical methods/technologies employed, for their analysis. A total of 214 papers were noted, with a total of 21 review articles (9.8%). Of this total, a surprisingly high number were from South Africa alone: 117 (54.7%), of which 44 (20.6%) reports were associated with South Africa’s Water Research Commission (WRC). The top three CECs research gaps were (decreasing rank: Number of “gaps”, %): 1) Toxicity/Risk/Impact (260, 21.5%), 2) Analysis/Tests/Methods (118, 9.8%) and 2) Future research/studies (118, 9.8%), and 3) Monitoring (89, 7.4%). The common classes of CECs that were reported on, were : (i) Chemical: pharmaceuticals, personal care products, steroids, chlorinated and brominated contaminants, PAHs, PCBs, phthalates, alkyl phenols, herbicides, organochlorine pesticides, engineered nanomaterials and (ii) “Microbiological”: antibiotic resistance genes, human enteric bacteria and viruses, microbial pathogens (e.g., E Coli, rotavirus, Crypto, etc.), infectious biological water contaminants (e.g., E Coli isolates), cyanobacterial blooms (Microcystis). Common test methods used for analysis of the chemical contaminants were found to be chromatography (gas, liquid)-mass spectrometry; for the microbial contaminants, they were culture-based methods, ELISA, fluorescence microscopy, qPCR, RT-qPCR, gel electrophoresis, Raman spectroscopy, and also chromatography (largely liquid)-mass spectrometry, were also used. Some proposals were additionally made to address the very common, significant research gaps noted in CECs research, especially the standardization of analytical chemical test methods, based on chromatography-mass spectrometry, for quantification.
Keywords: Contaminants of Emerging Concern